The Effect of Propulsion Style on Wrist Movement Variability During the Push Phase After a Bout of Fatiguing Propulsion. Issue 3 (4th July 2016) - Zukowski, Lisa A.; Christou, Evangelos A.; Shechtman, Orit; Hass, Christopher J.; Tillman, Mark D.
Abstract: Background: Wheelchair propulsion has been linked to overuse injuries regardless of propulsion style. Many aspects of the arcing (ARC) and semicircular (SEMI) propulsion styles have been compared, but differences in intracycle movement variability, which have been linked to overuse injuries, have not been examined. Objective: To explore how ARC and SEMI affect changes in intracycle wrist movement variability after a fatiguing bout of propulsion. Design: Repeated measures crossover design. Setting: Wheelchair rollers and wheelchair fatigue course in a research laboratory. Participants: Twenty healthy, nondisabled adult men without previous wheelchair experience. Interventions: Participants learned ARC and SEMI and used each to perform a wheelchair fatigue protocol. Main Outcome Measurements: Thirty seconds of propulsion on rollers were recorded by motion‐capture cameras before and after a fatigue protocol for each propulsion style on 2 testing days. Angular wrist orientations (flexion/extension and radial/ulnar deviation) and linear wrist trajectories (mediolateral direction) were computed, and intracycle movement variability was calculated as standard deviations of the detrended and filtered values during the push phase beginning and end. Paired samples t tests were used to compare ARC and SEMI based on the percent changes from pre‐ to postfatigue protocol. Results: Both propulsion styles resulted in increased intracycle wrist movement variability postfatigue, but observed increases did not significantly differ between ARC and SEMI. Conclusions: This study evinces that intersubject variability exceeded average changes in intracycle wrist movement variability for both propulsion styles. Neither propulsion style resulting in a greater change in intracycle movement variability may suggest that no single propulsion style is ideal for everyone. The large intersubject variability may indicate that the propulsion style resulting in the smallest increase in intracycle movement variability after a fatiguing bout of propulsion may differ for each person and may help explain why wheelchair users self‐select to use different propulsion styles.